2018
DOI: 10.1186/s13661-018-0944-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple positive solutions to singular positone and semipositone m-point boundary value problems of nonlinear fractional differential equations

Abstract: In this paper, we consider the properties of Green's function for the nonlinear fractional differential equation boundary value problemis the standard Riemann-Liouville derivative. Here our nonlinearity f may be singular at u = 0. As an application of Green's function, we give some multiple positive solutions for singular positone and semipositone boundary value problems by means of the Leray-Schauder nonlinear alternative and a fixed point theorem on cones. MSC: 34B15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…To construct the cone in a space such as C[0, T], usually a positive Green's function for the BVP is required to ensure a positive kernel for the integral operator. Consequently, it leads to existence of positive solutions for the original BVP [12,17,21,23,24,26]. Changing sign solutions have drawn relatively less attention.…”
Section: Theorem 12 ([10]mentioning
confidence: 99%
“…To construct the cone in a space such as C[0, T], usually a positive Green's function for the BVP is required to ensure a positive kernel for the integral operator. Consequently, it leads to existence of positive solutions for the original BVP [12,17,21,23,24,26]. Changing sign solutions have drawn relatively less attention.…”
Section: Theorem 12 ([10]mentioning
confidence: 99%
“…As a branch of q-calculus, fractional q-calculus was first proposed by Al-Salam and Agarwal in the 1960s; see [2,3]. Fractional q-calculus has a wide range of applications in many fields, such as cosmic strings and black holes, quantum theory, aerospace dynamics, biology, economics, control theory, medicine, electricity, signal processing, image processing, biophysics, blood flow phenomenon, and so on; see [4][5][6][7][8][9][10] and the references therein. The fractional q-difference equations are very important, and their basic theory has been continuously developed.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional calculus has played an important role in the modeling of different physical and natural phenomena, such as fluid mechanics, control system, and many other branches of engineering. In recent years, there are many papers concerning the existence of positive solutions for nonlinear fractional differential equations; see [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [2] showed the existence of multiple positive solutions to singular positone and semipositone m-point boundary value problems of nonlinear fractional differential equations 0 + ( ) + ( , ( )) = 0, 0 < < 1, (0) = 0,…”
Section: Introductionmentioning
confidence: 99%